Therapy for Pulmonary Arterial Hypertension: Glance on Nitric Oxide Pathway - Tettey, Abraham; Jiang, Yujie; Li, Xiaohui; Li, Ying (Frontiers in Pharmacology, 2021)
Pulmonary arterial hypertension (PAH) is a severe disease with a resultant increase of the mean pulmonary arterial pressure, right ventricular hypertrophy and eventual death. Research in recent years has produced various therapeutic options for its clinical management but the high mortality even under treatment remains a big challenge attributed to the complex pathophysiology. Studies from clinical and non-clinical experiments have revealed that the nitric oxide (NO) pathway is one of the key pathways underlying the pathophysiology of PAH. Many of the essential drugs used in the management of PAH act on this pathway highlighting its significant role in PAH. Meanwhile, several novel compounds targeting on NO pathway exhibits great potential to become future therapy medications. Furthermore, the NO pathway is found to interact with other crucial pathways. Understanding such interactions could be helpful in the discovery of new drug that provide better clinical outcomes.